B-mode ultrasonography biometry of the Amazon Parrot (Amazona aestiva) eye - Lehmkuhl, Ricardo C. [UNESP]; Almeida, Mariana F.; Mamprim, Maria Jaqueline [UNESP]; Vulcano, Luiz Carlos [UNESP] (Wiley-Blackwell, 2010)
PurposeUltrasonographic evaluation of the eye is a relatively recent addition to routine ophthalmic diagnostics in small animal ophthalmology. Some parameters for ophthalmic biometry have been established. There are few studies in clinical avian ophthalmology that describe ultrasound images of eye in some nocturnal avian species and in other birds that do not belong to the Brazilian fauna, but the psittacine family is not represented. The purpose of this study was to describe the following measurements: the distances between cornea and anterior lens capsule (D1) between the anterior and posterior lens capsule (D2), between posterior lens capsule and optic papilla (D3) and the axial length.MethodSixty four transpalpebral ocular ultrasound examinations were performed on 32 Blue fronted Amazon parrots (Amazona aestiva) with no history of previous ophthalmic disease.Result and DiscussionThe measurements were taken in sagital planes using a 10 MHz linear probe without a standoff pad. The mean values for the left eye were; D1 0.17 +/- 0.03 cm, D2 0.35 +/- 0.02 cm, D3 0.73 +/- 0.04 cm and the axial length 1.26 +/- 0.06 cm. In the right eye D1 0.17 +/- 0.02 cm, D2 0.34 +/- 0.02 cm, D3 0.74 +/- 0.03 cm and the axial length 1.25 +/- 0.05 cm. No significant statistical difference was observed among the birds or between the left and right eye. The description of these parameters will allow the veterinary practitioner to evaluate the structural changes that specific diseases may cause in these animals.
Keywords: Amazona aestiva; biometry; B-mode; eye; Psittacidae; ultrasound